2017
DOI: 10.1038/s41598-017-00554-5
|View full text |Cite
|
Sign up to set email alerts
|

Problems with visual statistical learning in developmental dyslexia

Abstract: Previous research shows that dyslexic readers are impaired in their recognition of faces and other complex objects, and show hypoactivation in ventral visual stream regions that support word and object recognition. Responses of these brain regions are shaped by visual statistical learning. If such learning is compromised, people should be less sensitive to statistically likely feature combinations in words and other objects, and impaired visual word and object recognition should be expected. We therefore teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 122 publications
(135 reference statements)
2
66
1
Order By: Relevance
“…For instance, pure alexia is a selective disorder of reading and occurs as a consequence of damage to the left occipitotemporal cortex-the so-called visual word form area (VWFA; Dehaene & Cohen, 2011 disputed the selectivity of this disorder by demonstrating that individuals with pure alexia are also impaired in recognizing other visual stimuli (Behrmann, Nelson, & Sekuler, 1998;Roberts et al, 2013;Roberts et al, 2015), which also elicit activation in the VWFA in neurologically intact participants (for review and a computational implementation, see , 2014Price & Devlin, 2011). Interestingly, individuals with DD have also been reported to show a hypo-activation of the VWFA and an impairment in processing non-verbal visual stimuli (e.g., Sigurdardottir et al, 2017) as, for instance, faces (e.g., Gabay et al, 2017). The measure of processing speed in WISC-IV uses non-verbal visual stimuli and the difficulties shown by children with DD on this task confirm a domain general impairment, supporting the predications of the triangle model (Woollams, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, pure alexia is a selective disorder of reading and occurs as a consequence of damage to the left occipitotemporal cortex-the so-called visual word form area (VWFA; Dehaene & Cohen, 2011 disputed the selectivity of this disorder by demonstrating that individuals with pure alexia are also impaired in recognizing other visual stimuli (Behrmann, Nelson, & Sekuler, 1998;Roberts et al, 2013;Roberts et al, 2015), which also elicit activation in the VWFA in neurologically intact participants (for review and a computational implementation, see , 2014Price & Devlin, 2011). Interestingly, individuals with DD have also been reported to show a hypo-activation of the VWFA and an impairment in processing non-verbal visual stimuli (e.g., Sigurdardottir et al, 2017) as, for instance, faces (e.g., Gabay et al, 2017). The measure of processing speed in WISC-IV uses non-verbal visual stimuli and the difficulties shown by children with DD on this task confirm a domain general impairment, supporting the predications of the triangle model (Woollams, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Frost et al (2013) found that, in English L1 speakers, SL positively correlated with the ability to learn the structural properties of Hebrew (L2), a Semitic language that follows different statistical properties than those usually found in Indo-European languages. In addition to these studies, the link between SL and literacy is supported by the finding that individuals with dyslexia seem to show SL impairments (e.g., Gabay, Thiessen, & Holt, 2015;Sigurdardottir et al, 2017;but see R€ usseler, Gerth, & M€ unte, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…Here also, the prediction is that a SL deficit may explain some of the difficulties these populations have with language processing and that they would therefore be characterized by impaired SL abilities. Special focus was directed to estimating SL abilities of individuals with dyslexia (Gabay, Thiessen, & Holt, ; Kahta & Schiff, ; Sigurdardottir et al, ), specific language impairment (Mainela‐Arnold & Evans, ), and agrammatism (Christiansen, Louise Kelly, Shillcock, & Greenfield, ), all reporting some degree of impaired SL performance among these clinical samples (see Saffran, for review). Together, then, all of these individual‐differences studies point to a clear pattern, supporting the involvement of SL in language…”
Section: Introductionmentioning
confidence: 99%